2011
DOI: 10.1007/s11104-011-0849-0
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of net nitrification associated with soil aggregates under conventional and no-tillage in a subtropical rice soil

Abstract: Tillage effects on soil nitrification kinetics at the aggregate scale were studied for a subtropical rice soil. Soil samples were separated into large aggregates (>2.0 mm), macro-aggregates (2.0-0.25 mm), micro-aggregates (0.25-0.053 mm) and silt + clay fractions (<0.053 mm) by wet-sieving. The net nitrification process was simulated by a zero-and first kinetics model. Conventional tillage (CT) increased the proportion of the silt + clay fraction by 60% and decreased large-aggregates by 35% compared to ridge w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Aggregate sizes had a significant effect on the nitrification rate (Jiang et al, 2011). In the present study, higher nitrification rates were found in 2-4 mm aggregates than in the other three aggregates under both N addition treatments.…”
Section: Variability Of Nitrification Associated With Soil Aggregate supporting
confidence: 49%
See 1 more Smart Citation
“…Aggregate sizes had a significant effect on the nitrification rate (Jiang et al, 2011). In the present study, higher nitrification rates were found in 2-4 mm aggregates than in the other three aggregates under both N addition treatments.…”
Section: Variability Of Nitrification Associated With Soil Aggregate supporting
confidence: 49%
“…Muruganandam, Israel & Robarge (2010) found that a higher nitrification rate associated with 0.5-1 mm aggregates than 2-4 and <0.25 mm aggregates. In addition, Jiang et al (2011) reported that nitrification rates were higher for the 2-0.25 mm fraction than the 0.25-0.053 mm fraction. We further separated the 0.25-2 mm aggregates into 0.25-1 and 1-2 mm aggregates and found higher nitrification rates in the 1-2 mm aggregates.…”
Section: Variability Of Nitrification Associated With Soil Aggregate mentioning
confidence: 99%
“…This change could be attributed to inhibited methanotrophic activity induced by aggregate destruction under tillage, or alternatively, to a smaller quantity of anoxic microsites within the no-tillage macro-aggregates maintained by intra-aggregate pore architecture and connectivity (e.g., Brewer, Calderón, Vigil, & Fischer, 2018). In contrast, both Jiang, Shi, Liu, and Wright (2011) and Plaza-Bonilla et al (2014) reported that soil tillage did not affect aggregate N 2 O production. tionship (e.g., Ebrahimi & Or, 2018), many abiotic and biotic factors that could regulate aggregate reactivity have not been studied.…”
Section: Context Of Global Changementioning
confidence: 99%
“…fungal hyphae and roots). The hierarchical order of aggregates might lead to the differences in the distribution and availability of soil organic matter (SOM) 22 26 . Previous studies have shown that land use can affect the C and N within aggregates, and the degree of its influence depends on soil texture and management measures 3 4 27 .…”
mentioning
confidence: 99%